Attenuation of the cardiovascular and metabolic complications of obesity in CD14 knockout mice - Roncon-Albuquerque R Jr (2008)
Aims: Although toll-like receptors (TLR) are known to mediate the metabolic complications of obesity, the mechanisms underlying its activation remain largely unknown. The present study analyzed a model of dietinduced obesity in mice lacking the TLR4/TLR2 co-receptor CD14. Main methods: Six-week-old male mice lacking CD14 (n= 16) were allocated to either a control diet or a high-fat high-simple carbohydrate diet (5.4 kcal/g; 35% fat; 35% sucrose), and compared with C57BL/6 (WT; n = 15) controls. After 12 weeks, body composition, basal sympathetic activity, non-invasive blood pressure and glucose tolerance were evaluated. Hepatic and adipose tissues were collected for mRNA quantification, histology and LPS incubation. Key findings: In both WT and CD14 knockout mice, obesity was accompanied by TLR2 and TLR4 upregulation. However, obese mice lacking CD14 presented decreased lipid and macrophage content in hepatic and adipose tissues, lower urinary levels of noradrenaline, decreased systolic blood pressure, reduced fasting plasma glucose and blunted glucose intolerance, compared with obese WT group. In the presence of exogenous sCD14, adipose tissue incubation with LPS-induced TLR2 and TNF-alpha upregulation in both WT and CD14 knockout obese mice. Significance: In our model of diet-induced obesity, mice lacking CD14 showed lower adiposity and hepatic steatosis, improved glucose homeostasis, blunted sympathetic overactivity and reduced blood pressure elevation. This was observed in the presence of preserved TLR4 and TLR2 gene expression, and intact TLR4 signaling pathways. These results suggest that CD14-mediated TLR activation might contribute to the cardiovascular and metabolic complications of obesity.